Modification of sludge biochar by MnO2 to degrade methylene blue: Synergistic catalysis and degradation mechanisms. (August 2022) - Li, Yuanping; Liu, Yuqing; Liu, Yihuan; Chen, Yaoning; Chen, Li; Yan, Haoqin; Chen, Yanrong; Xu, Fangting; Li, Meiling; Li, Linshenzhang
Abstract: In this study, sludge biochar (SBC) was prepared by pyrolysis method, MnO2 and MnO2 @SBCs with different MnO2 /SBC mass ratios (3%, 5%, 10% and 20%) were synthesized by co-precipitation method. The catalytic performance was examined by activating peroxymonosulfate (PMS) for methylene blue (MB) degradation. MB can be completely removed within 30 min when the mass ratio of MnO2 /SBC is greater than 5% and the degradation kinetics of MB is more in line with the pseudo-first-order kinetic model in the MnO2 @SBC/PMS system. Besides, the pseudo-first-order kinetic constants ( k ) in MnO2 @SBC/PMS are significantly higher than that in SBC/PMS and MnO2 /PMS, and the largest degradation rate of MB is in 5% MnO2 @SBC/PMS system. MnO2 @SBC exhibited excellent PMS activation ability in a wide range of pH (5–9) with complete degradation of MB in 30 min. Furthermore, MnO2 @SBC has good stability after five usages still activating PMS for complete degradation of MB in 180 min. The quenching experiments and EPR spectrum indicated that both SO4 −, OH and 1 O2 were the main reactive oxygen species. Finally, the probable MB degradation pathway was proposed in the MnO2 /PMS system. This study provides a reliable insight into sludge resource utilization, sludge biochar modification and its catalytic performance improvement. Graphical abstract: Unlabelled Image Highlights: MnO2 @SBC with different MnO2 /SBC mass ratios (3%, 5%, 10% and 20%) were prepared. 5% MnO2 @SBC showed excellent PMS activation for MB completely degradation in 30 min. SO4 −, OH and 1 O2 are synergistically contributed for the degradation MB. MB degradation pathway and the synergistic catalytic mechanism are proposed.